The spectator's active participation in "YO SOY. Homenaje a las mujeres rapadas" by Art al Quadrat - Molanes Rial, Mónica (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The purpose of the work is to analyze how the spectator's participation in the performance YO SOY. Homenaje a las mujeres rapadas is pojected as a tool for political upheaval in public space around two central issues, trauma and memory, examined from artistic practice.
Keywords: spectator; participation; performance; repression; memory; women